Studies of beauty baryon decays to $D^0 p h^-$ and $Λ_c^+ h^-$ final states - collaboration, L; Aaij, R; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; et al. (2013)
Decays of beauty baryons to the $D^0 p h^-$ and $Λ_c^+ h^-$ final states (where $h$ indicates a pion or a kaon) are studied using a data sample of $pp$ collisions, corresponding to an integrated luminosity of 1.0 fb$^{-1}$, collected by the LHCb detector. The Cabibbo-suppressed decays $Λ_b^0→ D^0 p K^-$ and $Λ_b^0→ Λ_c^+ K^-$ are observed and their branching fractions are measured with respect to the decays $Λ_b^0→ D^0 p π^-$ and $Λ_b^0→ Λ_c^+ π^-$. In addition, the first observation is reported of the decay of the neutral beauty-strange baryon $Ξ_b^0$ to the $D^0 p K^-$ final state, and a measurement of the $Ξ_b^0$ mass is performed. Evidence of the $Ξ_b^0→ Λ_c^+ K^-$ decay is also reported.